Метод розміщення сповіщувачів провідно-безпровідної системи пожежної сигналізації всередені будівлі - Куценко, С. В.; Бакарджиєв, Роман Олександрович; Бакарджиев, Роман Александрович; Bakardzhyiev, Roman; Корецька, О. О.; Мусієнко, М. П. (Чорном. держ. ун-т ім. Петра Могили, 2017)
UK: У статті розглянутий розроблений метод розміщення пожежних сповіщувачів все-редині будівлі для побудови ефективних провідно-безпровідних пожежних сигналізацій. Розроблено програмний продукт, в якому реалізовані отримані положення. Проведені підрахунки, які показали виграш у зменшенні кількості модулів при застосуванні запро-понованого методу розміщення пожежних сповіщувачів. EN: The article considers the developed method of placing fire detectors inside a building to build efficient wire-wireless fire alarms. The analysis of technical problems arising during the construction of a fire network is analyzed. The issues related to the selection of the necessary equipment are considered. A software product has been developed in which the received provisions are realized. Calculations were carried out, which showed a gain in reducing the number of modules when applying the proposed method for placing fire detectors. An example of the work of a software product is given.
Method of placing the detectors of wire-wireless fire alarm system inside the building
Keywords: пожежний сповіщувач; стельові та настінні сповіщувачі; провідний та безпровідний зв’язок